Effects of physical exercise on skeletal muscles of rats with cerebral ischemia - Melo,R.T.R. (2019)
Physical exercise is a known preventive and therapeutic alternative for several cerebrovascular diseases. Therefore, the objective of the present study was to evaluate the motor performance and histomorphometry of the biceps brachii, soleus, and tibialis anterior muscles of rats submitted to a treadmill training program prior to the induction of cerebral ischemia via occlusion of the middle cerebral artery (OMCA). A total of 24 Wistar rats were distributed into four groups: Sham-Sed: sedentary control animals (n=6), who underwent sham surgery (in which OMCA did not occur); Sham+Ex: control animals exercised before the sham surgery (n=6); I-Sed: sedentary animals with cerebral ischemia (n=6); and I+Ex: animals exercised before the induction of ischemia (n=6). The physical exercise consisted of treadmill training for five weeks, 30 min/day (5 days/week), at a speed of 14 m/min. The results showed that the type-I fibers presented greater fiber area in the exercised ischemic group (I+Ex: 2347.96±202.77 µm2) compared to the other groups (Sham-Sed: 1676.46±132.21 µm2; Sham+Ex: 1647.63±191.09 µm2; I+Ex: 1566.93±185.09 µm2; P=0.0002). Our findings suggested that the angiogenesis process may have influenced muscle recovery and reduced muscle atrophy of type-I fibers in the animals that exercised before cerebral ischemia.